Employers' views on the importance of English proficiency and communication skill for employability in Malaysia - Ting, Su Hie; Ernisa, Marzuki; Kee-Man, Chuah; Jecky, Misieng; Jerome, Collin (Universiti Malaysia Sarawak, 2017)
Employability of graduates is a concern in many countries, including Malaysia, and the high unemployment rate among graduates is often attributed to their lack of English proficiency and communication skills. These two distinctive elements are often collated, and it is important to find out which is more important to employers. The study examined the employers’ views on the importance of English proficiency and communication skill for graduates to be employed in the Malaysian private sector. The data were from semi-structured interviews conducted with 10 employers in the private sector who were in the position to recruit staff. The 21,433-word interview transcripts were analyzed. The results revealed that employers in the Malaysian private sector view language proficiency and communication skills as separate qualities. The employers are willing to consider employing candidates with average English proficiency if they have good communication skills, except for jobs which require more communication in English such as customer service and marketing. The results also revealed that good communication skills can increase employability and opportunities for career advancement. The findings highlight the communication skills that universities need to emphasize so that their graduates have the necessary skills to perform well in employment interviews and in their work.